Δ2H of wheat and soil water in different growth stages and their application potentialities as fingerprints of geographical origin. (1st July 2017) - Liu, Hongyan; Wei, Yimin; Wei, Shuai; Jiang, Tao; Zhang, Senshen; Guo, Boli
Highlights: δ 2 H values of defatted wheat, soil water, rainwater and groundwater were determined. δ 2 H in wheat, soil water and rainwater changed consistently among different regions. δ 2 H in wheat was significantly correlated with the δ 2 H in soil water above 20 cm. Both wheat and soil water (0–20 cm) in the maturity might be used as fingerprints. Abstract: The study aims to investigate whether stable hydrogen isotopic ratio ( δ 2 H) in wheat and soil water can be used as the fingerprint for geographical origin of wheat. Wheat was planted in three different regions in China across two years. The δ 2 H values were determined for soil water in three growth periods, and rainwater, groundwater, and defatted wheat in the maturity stage. The δ 2 H values both in soil water and defatted wheat showed significant differences among different regions and the changing trend of δ 2 H value in wheat was consistent with that in soil water and rainwater, but different from that in groundwater. The δ 2 H values in soil water in the depth of 0–20 cm in the maturity stage were positively correlated to the δ 2 H values of defatted wheat (y = 0.205x − 52.628, r 2  = 0.645) and could be used as the potential indicator for tracing wheat geographical origin.